On the Distribution and Biology of Varanus Mabitang - Gaulke, Maren; Altenbach, Alexander Volker; Demegillo, Arnold; Struck, Ulrich (Silliman Journal, 2022)
During the past two years, our knowledge on the distribution, morphology, and biology of the Mabitang (Varanus mabitang) has enhanced significantly. Captured Varanus mabitang were examined and marked permanently by passive integrated transponders before being released. While the first recapture provided initial information on activity range, observations of live animals, the examination of feces, and isotope analyses revealed a dominant frugivorous diet, comprising a minimum of 16 different food plants. Invertebrates such as crabs, insects, and snails are an additional food source for V. mabitang. Sightings and spoor of V. mabitang show that this animal is rare, but not as rare as originally feared. It is confined to primary forests and only rarely can be seen in secondary growth areas adjacent to primary forests. Results of distribution surveys on neighboring islands leave little hope that this animal exists outside of Panay.